Experimental prediction of the noncontact jet Trencher's excavation depth in clay. Issue 2 (17th February 2017) - Zhang, Shusen; Wang, Chun; Ge, Tong
ABSTRACT: Trenching depth calculation of traveling jet is a very important field in both pipeline burying and dredging engineering. The trenching ability of a noncontact control flow jet trencher was predicted by experimental method according to the geometry similarity. In the test, the jet pressure, the shear strength of clay, and the translational speed of nozzle were the same with the design parameters, while the nozzle was a reduced scale model. The trenching depth was found about seven to nine times of the nozzle's diameter. The width of the trench was about four times of the nozzle's diameter. Based on the test results the noncontact jet trencher was produced and succeeded in practical usage.